SIMULATION OF THE STRESS OF RELAXATION OF STRESSES IN THE LUBRICANT FILM ON THE SURFACE OF FRICTION IN THE PRESENCE OF FULLERENES IN THE LUBRICANT - Войтов, Віктор Анатолійович; Кравцов, Андрій Григорович; Войтов, Антон Вікторович (Problems of Friction and Wear, 2021)
The paper presents the results of theoretical studies on the formation of a lubricating film on the friction surface in the presence of fullerenes in the lubricant. Based on the analysis of literature sources, it is proved that the friction surface, which in the process of operation of the tribosystem is an "electrostatic field generator", encourages a change in the structural viscosity of the lubricating film. Increasing the rate of dissipation in the tribosystem leads to an increase in the magnitude of the electrostatic field of the friction surface, which promotes the formation of micelles of fullerenes of the framework. The results of modeling the change in the values of the life time of the actual contact spot, as well as the relaxation time of stresses on the actual contact spot in the presence on the friction surface of a lubricating film having a gel structure. Parametric identification of the macro reological model of stress relaxation in the lubricating film on the actual contact spots is performed. Theoretical dependences of the change in the life time of the actual contact spot and the stress relaxation time on the values of the dissipation rate and the concentration of the fullerene composition are obtained. It is proved that the value of the relaxation time is a measure of the transition of the viscous properties of the structure of the lubricating film into elastic properties and, conversely, elastic into viscous. It is shown that the driving force of the transition is the rate of dissipation in the tribosystem, which can be called the pumping energy. The results of modeling these parameters allow us to assert the existence of values of the rate of dissipation, at the achievement of which on the friction surface begins to form a gel structure (structure in the form of a framework), which perceives the load as a solid. At small values of the rate of dissipation of the pumping energy is not enough to form the structure of the gel and the lubricating film will have the structure of the sol and perceive the load as a viscous body.